Crossing the Thrashold: The Hero's Journey and "Assassin's Creed: Valhalla" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
In the last decades, the video ludic medium growth has been reaching peaks untouched by anything before in the media history. We can consider video games the new way, the way of the contemporaneity, to tell stories, to narrate, to live fictional experiences. This paper aims to investigate the characteristics of video games and the reasons that make this medium so appetible for so many users. We will analyze the video games history, linking them to Joseph Campbell’s theorizations on the monomith, trying to catch the virtual version of “a hero ventures forth from the world of common day into a region of supernatural wonder” (Campbell 2004, p. 28). Following up, we will try to underline the potential analogy between the hero of the journey and the gamer itself, since the latter too is, in some ways, leaving the common day world in order to answer to the call of a magical world. We will analyze some specific characteristics of video games in general and we will then focus on Assassin’s Creed: Valhalla (Ubisoft, 2020). In fact, in this product it is possible to recognize many conjunction point between the journey, the heroism, the divine incarnation, and the openness to mythological worlds full of wonders.
Keywords: Epic Videogames; Hero's Journey; Monomyth; Player Experience; Fictional worlds